Optimal Contracts with Randomly Arriving Tasks. Issue 637 (29th October 2020) - Bird, Daniel; Frug, Alexander
Abstract: Workers are rarely assigned to perform the same task throughout their career. Instead, their assignments may change randomly over time to comply with the fluctuating needs of the organisation where they are employed. In this article, we show that this typical randomness in workplaces has a striking effect on the structure of long-term employment contracts. In particular, simple intertemporal variability in the worker's tasks is sufficient to generate a rich promotion-based dynamics in which, occasionally, the worker receives a (permanent) wage raise and his future work requirements are reduced.